2008
DOI: 10.1186/1471-2407-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Lymph vascular invasion in invasive mammary carcinomas identified by the endothelial lymphatic marker D2-40 is associated with other indicators of poor prognosis

Abstract: Background: Immunohistochemical studies of lymphatic vessels have been limited by a lack of specific markers. Recently, the novel D2-40 antibody, which selectively marks endothelium of lymphatic vessels, was released. The aim of our study is to compare lymphatic and blood vessel invasion detected by hematoxylin and eosin (H&E) versus that detected by immunohistochemistry, relating them with morphologic and molecular prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 39 publications
(62 reference statements)
6
36
2
1
Order By: Relevance
“…Presence of lymphovascular invasion in a primary tumor has been used as an indication for the ability of this tumor to metastasis outside the breast. 1 Such tumors therefore receive more intense therapy than tumors with no lymphovascular invasion in the same disease stage. [2][3][4] The term 'lymphovascular invasion' refers to invasion of either blood vessels or lymph vessels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of lymphovascular invasion in a primary tumor has been used as an indication for the ability of this tumor to metastasis outside the breast. 1 Such tumors therefore receive more intense therapy than tumors with no lymphovascular invasion in the same disease stage. [2][3][4] The term 'lymphovascular invasion' refers to invasion of either blood vessels or lymph vessels.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In previous reports, LI was found to be independent poor prognostic factor in lymph node (LN)-negative breast cancer patients and has been recommended to be added to clinical management tools such as the 'Nottingham Prognostic Index (NPI)'. 8 However, there still remains controversy in the literature regarding the relevance of assessment of vascular invasion in LN-positive BC.…”
mentioning
confidence: 99%
“…Among known markers of lymphatic vessel endothelium, podoplanin seems to be the most promising [2]. It allows for assessment of microvessel density and demonstration of lymphovascular invasion [2][3][4][5][6][7][8][9]. However, there is no standardized method recommended for assessment of lymphangiogenesis [1].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that D2-40 is the most sensitive and specific antibody for the detection of lymphatic endothelium in different malignancies like gastric [19], colorectal [20], vulvar [21], breast [22] and endometrial cancer [23].…”
Section: Introductionmentioning
confidence: 99%